8(8+9g)=7(-2-11g)

Simple and best practice solution for 8(8+9g)=7(-2-11g) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(8+9g)=7(-2-11g) equation:


Simplifying
8(8 + 9g) = 7(-2 + -11g)
(8 * 8 + 9g * 8) = 7(-2 + -11g)
(64 + 72g) = 7(-2 + -11g)
64 + 72g = (-2 * 7 + -11g * 7)
64 + 72g = (-14 + -77g)

Solving
64 + 72g = -14 + -77g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '77g' to each side of the equation.
64 + 72g + 77g = -14 + -77g + 77g

Combine like terms: 72g + 77g = 149g
64 + 149g = -14 + -77g + 77g

Combine like terms: -77g + 77g = 0
64 + 149g = -14 + 0
64 + 149g = -14

Add '-64' to each side of the equation.
64 + -64 + 149g = -14 + -64

Combine like terms: 64 + -64 = 0
0 + 149g = -14 + -64
149g = -14 + -64

Combine like terms: -14 + -64 = -78
149g = -78

Divide each side by '149'.
g = -0.5234899329

Simplifying
g = -0.5234899329

See similar equations:

| 58/-16 | | 100+500x-100x^2=700 | | 6(v-6)=4v-22 | | 3r/2=-3 | | 2x+7y-11z=27 | | 4x+10=2x-30 | | 0=2x-150 | | 4.7=x-1.2 | | y=6+1.5z | | 7b-9=30 | | -25w3/42*-3w/10 | | 7(1/35x-2/7) | | x=120-(15x4)/(5x4) | | 7-2x=4x-3 | | (6)=7-4y | | X+2=18+8X-48 | | 3x+20=5x-10 | | 5-6y=6-7y | | -4-7-3x+4=24 | | 3.896-(-11.42)= | | n+8-6n=13 | | (6)-1=7-4y | | f(3/2)=2X-5 | | 3w+7=14+3x | | 3(m+1.5)=1.5 | | 2(6n-1)=-38 | | 3(2y+6)=-4[-3y-5(-y+10)] | | 2y-3z=12 | | 5(6x+1)=15 | | x-7/2-1=x-2/3 | | (6)-2=7-4y | | 6*3.14=2*3.14q |

Equations solver categories